Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

PDE's: For the partial differential equation u_tt = 9u_xx, a general solution is u(x,t) = F(x+3t)+G(x-3t). Find a particular solution with initial conditions u(x,0)=0, u_t(x,0)=sin(pi*x), u(0,t)=u(1,t)=0.

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SEE EXPERT ANSWER

To see the expert answer you'll need to create a free account at Brainly

I'm having trouble especially using/interpreting the last initial condition.
before we look at initial conditions do you know how to do this part: solve for particular solution \[u_{t t}=9u_{xx}\] ? is it separation of variables?
If the problem asked me to solve it, yeah I would use separation of variables since that's the only method I know so far. but the problem only stated that the given solution is indeed a solution. actually, the first part of this problem was to show that the given solution is indeed a solution, the second part is this.

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

ok
\[u(x,0)=F(x+3(0))+G(x-3(0))=F(x)+G(x)=0\] f(x)+g(x)=0 \[u_t=3f(x+3t)-3g(x-3t)\] \[u_t(x,0)=3f(x)-3g(x)=\sin(\pi x)\] \[u(0,t)=u(1,t)=0\] \[u(0,t)=F(0+3t)+G(0-3t)=F(3t)+G(-3t)=0\] \[u(1,t)=F(1+3t)+G(1-3t)=0\]
so we have \[F(x)+G(x)=0\] \[f(x)+g(x)=0\] \[3f(x)-3g(x)=\sin(\pi x)\] \[F(3t)+G(-3t)=0\] \[F(1+3t)+G(1-3t)=0\]
\[f(x)+g(x)=0 => f(x)=-g(x) =>3f(x)+3f(x)=\sin(\pi x)\]
\[f(x)=\frac{1}{6} \sin(\pi x)\]
F(x)=\[\int\limits_{}^{}f dx=\int\limits_{}^{}\frac{1}{6} \sin(\pi x) dx=-\frac{1}{6} \cos(\pi x) +c_1\]
\[3f(3t)-3g(-3t)=0 => f(3t)-g(-3t)=0 => f(3t)=g(-3t)\] \[3f(1+3t)-3g(1-3t)=0 => f(1+3t)=g(1-3t)\] i hope some of this will help i have to leave
thanks still! ill look at it
you might want to check what i wrote for mistakes gl

Not the answer you are looking for?

Search for more explanations.

Ask your own question